Could mitochondria help athletes to make gains? - King, A. (Nature, 2021)
Usain Bolt won the men`s 100 metre final in the 2016 Olympic Games in 9.81 seconds and 42 strides. A few days later, Eliud Kipchoge ran 42 kilometres in 2 hours and 8 minutes to win the marathon. These extraordinary feats pose very different challenges for the human body, but the races began in much the same way. As the starting pistol fired, Bolt and Kipchoge began to use creatine phosphate, an energy-rich molecule stored in muscle tissue, to generate the energy-carrying molecule ATP. In a few seconds, however, both athletes` stores of creatine phosphate were depleted, forcing their bodies to break down glucose to provide ATP to contracting muscle cells for a few more minutes. For Bolt and his fellow sprinters, a few minutes seems like an age. But for marathon runners, there is much farther to go. To reach the finish line, these endurance athletes rely on a slower, but more efficient way to generate ATP that uses oxygen to burn fats and carbohydrates, in structures inside the cell called mitochondria. Elite endurance athletes such as Kipchoge pack many more of these aerobic power plants into muscle cells than both an average person and the far-from-average Usain Bolt. "He probably doesn`t need any more mitochondria than you or I," says John Hawley, an exercise physiologist at the Australian Catholic University in Melbourne. Athletes` mitochondrial engines activate quickly, within a few minutes of exercise, but even for the best, that switch doesn`t flick immediately. "We can`t turn on mitochondria fast enough to provide all the energy required for a sprint," says David Hood, a mitochondrial scientist at York University in Toronto, Canada. All elite athletes push themselves to the limit in search of small advantages, and for endurance athletes the mitochondria are a target for making marginal gains. Exercise scientists are working to better understand how these structures, found inside nearly all cells, adapt to exercise, and how to improve their delivery of oxygen. Their findings are beginning to inform training regimes, and might have therapeutic uses for non-athletes — perhaps allowing the delivery of some of the benefits of exercise through a pill.